EKONOMI SIRKULAR DALAM INDUSTRI MANUFAKTUR: STRATEGI UNTUK MENGURANGI LIMBAH DAN MENINGKATKAN EFISIENSI - Sari, Urmila; Rusdiantini, Sansy; Novianti, Sri; Maulidiah, M (Pusat Riset dan Publikasi, 2025)
Continuous population growth and consumption have pushed the manufacturing industry to face significant challenges related to resource and waste management. The linear economic model of